2017
DOI: 10.1016/j.tox.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related gene polymorphisms in pulmonary diseases

Abstract: Between the DNA sequences of two randomly-selected human genomes, which consist of over 3 billion base pairs and twenty five thousand genes, there exists only 0.1% variation and 99.9% sequence identity. During the last couple of decades, extensive genome-wide studies have investigated the association between single-nucleotide polymorphisms (SNPs), the most common DNA variations, and susceptibility to various diseases. Because the immune system's primary function is to defend against myriad infectious agents an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 145 publications
(142 reference statements)
0
12
0
Order By: Relevance
“…50 Numerous SNPs in alpha 1-antitrypsin, tumor necrosis factor, microsomal epoxide hydrolase, glutathione S-transferase, interleukin-6, interleukin-8 genes have been studied in terms of association with COPD susceptibility, severity, phenotypes, drug response, or comorbidities, but with conflicting results and limitations of the studies. 51,52 In 2009, two case-control studies comprising 1488 participants, conducted by He et al 30 revealed that out of seven IL-6 SNPs, four were associated with COPD, while the rs1800797 allele was associated with a rapid decline in lung function. Another European study investigated the relationship between rs1800797, rs1800795, and rs1800796 and the susceptibility for the disease, the lung function, and hypoxemia level and concluded that rs1800797 and rs1800795 were not associated with the disease, the frequency of genotypes containing the C allele was lower in COPD patients, and also that the GCG (-597, -174, -572) haplotype was associated with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…50 Numerous SNPs in alpha 1-antitrypsin, tumor necrosis factor, microsomal epoxide hydrolase, glutathione S-transferase, interleukin-6, interleukin-8 genes have been studied in terms of association with COPD susceptibility, severity, phenotypes, drug response, or comorbidities, but with conflicting results and limitations of the studies. 51,52 In 2009, two case-control studies comprising 1488 participants, conducted by He et al 30 revealed that out of seven IL-6 SNPs, four were associated with COPD, while the rs1800797 allele was associated with a rapid decline in lung function. Another European study investigated the relationship between rs1800797, rs1800795, and rs1800796 and the susceptibility for the disease, the lung function, and hypoxemia level and concluded that rs1800797 and rs1800795 were not associated with the disease, the frequency of genotypes containing the C allele was lower in COPD patients, and also that the GCG (-597, -174, -572) haplotype was associated with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…; obtained from ATCC) using TaqMan Gene expression assays (Thermo Fisher) for the NLRP1 , NLRP4 , and NLRP8 genes. The WI38 cell line was selected for the study because fibroblasts are believed to be the major cells responsible for the production and maintenance of the extracellular matrix, and fibroblasts from individuals with COPD have a reduced capability to sustain tissue repair [18]. The total RNA, from blood, was extracted using Trizol.…”
Section: Methodsmentioning
confidence: 99%
“…One particularly powerful approach to assess the role of some processes in humans is to investigate whether genetic variation influences susceptibility to infection. Single Nucleotide Polymorphisms (SNPs) are believed to be the true source of variability among humans (Pacheco and Moraes, 2009;Singh et al, 2017) and it is expected that the variants in genes involved in the pathogen-host interaction are influencing resistance/ susceptibility to the disease. Some reports have investigated SNPs in genes involved in the autophagy process, leading to important evidence about its role during human TB.…”
Section: Genetic Association Studies In Autophagy-related Genesmentioning
confidence: 99%